2013
DOI: 10.2478/eces-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Metal Nanoparticles and Plants / Nanocząstki Metaliczne I Rośliny

Abstract: Metal nanoparticles (MNPs) belong mostly to the engineered type of nanoparticles and have not only unique physical and chemical properties but also different biological actions. In recent years, noble MNPs and their nano-sized agglomerates (collectively referred to as nanoparticles or particles in the subsequent sections) have been the subjects of much focused research due to their unique electronic, optical, mechanical, magnetic and chemical properties that can be significantly different from those of bulk ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 75 publications
1
17
0
1
Order By: Relevance
“…Mushtaq (2011) also reported that Fe 3 O 4 , TiO 2 and carbon NPs cause negative effect on seed germination rate, root elongation and germination index of cucumber plant. On the positive side, NPs in plant species are reported to enhance seed germination frequency and growth of plant seedlings, root elongation, increase in root/shoot ratio among other physiological attributes (Masarovičová and Král'ová 2013). It is rather essential to administer appropriate doses of NPs in plant species for attaining beneficial effects.…”
Section: Characteristics Of Copper Cu-npsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mushtaq (2011) also reported that Fe 3 O 4 , TiO 2 and carbon NPs cause negative effect on seed germination rate, root elongation and germination index of cucumber plant. On the positive side, NPs in plant species are reported to enhance seed germination frequency and growth of plant seedlings, root elongation, increase in root/shoot ratio among other physiological attributes (Masarovičová and Král'ová 2013). It is rather essential to administer appropriate doses of NPs in plant species for attaining beneficial effects.…”
Section: Characteristics Of Copper Cu-npsmentioning
confidence: 99%
“…The development of nanomaterials is significant as it opened new vista in plant biotechnology and agriculture (Scrinis and Lyons 2007). Application of nanotechnology is found to target specific agricultural problems in plant pathogen interaction providing new ways for crop protection (Nair et al 2010) apart from possessing significant uses in medicine and life sciences (Patolsky et al 2006;Caruthers et al 2007; Masarovičová and Král'ová 2013). Cu-NPs are used as microfertilizers and pesticides (Selivanov and Zorin 2001;Raikova et al 2006).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Beside the above-mentioned nanofertilizers that supply essential nutrients to plants, also some other NPs, eg TiO 2 NPs, Al 2 O 3 NPs or single-walled or multiwall carbon nanotubes were found to have beneficial effect on plant growth [269][270][271]. Although titanium does not belong to essential plant nutrients, application of TiO 2 NPs was found to improve plant-photosynthesis efficacy, increase plant-enzyme activity and provide plants with more N nutrient by chemical fixation of N 2 in the air, thereby enhancing plant growth [272][273][274][275].…”
Section: Nanofertilizers and Plant Growth Stimulating Nanoparticlesmentioning
confidence: 99%